Measuring visitor learning outcomes from showcases, video installations, and interactive tablets: an empirical investigation. (3rd May 2020) - Zheng, Xia; Yang, Xuewen
ABSTRACT: Museums employ a diverse range of display models. The most common forms are 'showcases' and 'multimedia displays', which include video installations and the use of interactive tablets. This poses the question of how the learning outcomes differ between showcase and multimedia displays. Focusing on 308 adult visitors across four typologies, this research explores how the learning outcomes differ when similar information is displayed using showcase and multimedia (video installation and interactive tablet) approaches in two exhibitions. Participants were randomly divided into three groups: namely, the showcase, video, and interactive groups. Interviews, questionnaires, and follow-up interviews were conducted to determine the learning outcomes. Results show statistically different learning outcomes between showcase and video installation, but no significant difference between showcase and interactive tablets. Moreover, results confirm a correlation between visitor gender and learning outcome, as well as visitor gender and typologies, but no evident correlation between learning outcomes and visitor typologies. Besides, this study explores the interaction impact on learning outcomes of 120 visitors who watched both showcase and multimedia and results show a correlation between visitors' learning outcomes and different display models (showcase, multimedia and double-channel display).